Official debt restructurings and development. (November 2018) - Cheng, Gong; Díaz-Cassou, Javier; Erce, Aitor
Highlights: This paper exploits a new database on Paris Club official debt restructurings. The objectives pursued by the Paris Club were gradually broadened over time. Most of the operations completed through the Paris Club since the 1980s were collectively orchestrated. Nominal debt relief operations accelerate per capita GDP growth, reduce poverty and inequality. Official development assistance flows towards countries receiving nominal debt relief falls after a restructuring. Abstract: Despite the frequency of official debt restructurings, little systematic evidence has been produced on their characteristics and implications. Using a dataset covering more than 400 Paris Club agreements, this paper fills that gap. It provides a comprehensive description of the evolving characteristics of these operations and studies their impact on debtors. The progressive introduction of new terms of treatment gradually turned the Paris Club from an institution primarily concerned with preserving creditors' claims into an instrument to foster development in the world's poorer nations, among other objectives. Our study finds that more generous restructuring conditions involving nominal relief are associated with an acceleration of per capita GDP growth and with a reduction in poverty and inequality. We also find that countries receiving nominal relief tend to receive lower aid flows subsequently, the opposite being the case for countries receiving high reductions in the net present value of their obligations, but no nominal haircuts.